Low Prevalence of Severe Acute Respiratory Syndrome Coronavirus 2 Among Pregnant and Postpartum Patients With Universal Screening in Seattle, Washington. (30th May 2020) - LaCourse, Sylvia M; Kachikis, Alisa; Blain, Michela; Simmons, LaVone E; Mays, James A; Pattison, Amber D; Salerno, Carol C; McCartney, Stephen A; Kretzer, Nicole M; Resnick, Rebecca; Shay, Rosemary L; Savitsky, Leah M; et al.
Abstract: We found low prevalence of SARS-CoV-2 (2.7% [5/188]) among pregnant and postpartum patients with universal testing. Prevalence among symptomatic patients was similar under initial targeted screening (22.2% [4/18]) and universal approaches (19.1% [8/42]). Among 170 asymptomatic patients, 2 were positive or inconclusive, respectively; repeat testing at 24 hours was negative. Abstract : We found a low prevalence of severe acute respiratory syndrome coronavirus 2 among pregnant and postpartum patients after initiation of universal testing at University of Washington–affiliated hospitals using a combination of on-site rapid testing, high-throughput centralized testing, and outpatient drive-through screening prior to admission.